Correlates of Odonata species composition in Amazonian streams depend on dissimilarity coefficient and oviposition strategy - Calvão, Lenize B.; Siqueira, Tadeu [UNESP]; Faria, Ana Paula J.; Paiva, Carina K. S.; Juen, Leandro (Wiley, 2022)
Environmental and spatial heterogeneity affects the distribution of aquatic insects, determining or influencing the variation in local species composition. Dragonflies and damselflies (Odonata) have different strategies for oviposition site selection that depend on environmental conditions. However, Land Use and Land Cover (LULC) can reduce the availability of suitable sites for Odonata oviposition through environmental homogenization. We investigated the relationship between environmental and spatial heterogeneity and variation in species composition of Odonata with different oviposition strategies (endophytic, epiphytic and exophytic) in Amazonian streams in a gradient of LULC. We used the Jaccard and Bray-Curtis coefficients and the Manhattan distance to estimate a continuum of variation in species composition. Variation in the composition of endophytic and epiphytic species was explained by spatial heterogeneity. Using abundance data and the Manhattan distance, we found a relationship between variation in species composition and environmental heterogeneity. Endophytic species composition was related to perch heterogeneity, while exophytic species composition was related to perch and canopy cover heterogeneity. Exophytic and endophytic species could be used in biomonitoring as they respond to specific environmental predictors and because exophytic species do not have spatial patterns across the landscape. Different dissimilarity coefficients provide complementary information about the responses of multispecies communities to land use, as some will represent strong effects (presence-absence indexes) while others will represent more subtle effects (abundance-based indexes). Land use can increase the environmental heterogeneity of some predictors (perches and canopy cover). Physical changes in streams such as hydromorphological alterations can modify specific habitats, affecting oviposition strategies and supporting tolerant species.
Keywords: community variation; endophytic; epiphytic; exophytic oviposition strategy; habitat integrity